Effectiveness and safety of diagnostic flexi-rigid thoracoscopy in differentiating exudative pleural effusion of unknown etiology: a retrospective study of 215 patients - Gao, Bao-An; Zhou, Gang; Guan, Li; Zhang, Ling-Yun; Xiang, Guang-Ming (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Background: The aim of this study was to evaluate the effectiveness and safety of diagnostic flexi-rigid thoracoscopy in differentiating exudative pleural effusion of unknown etiology. Methods: A total of 215 patients with undiagnosed exudative pleural effusion were consecutively recruited between January 2011 and February 2013. Thoracoscopy was carried out under local anesthesia, and multisite pleural biopsies were performed using a flexi-rigid thoracoscope. The tolerance of the patients, surgical complications and postoperative pathological diagnosis rate were used to evaluate the effectiveness and safety of the thoracoscopy procedures. Results: All patients, Karnofsky performance status (KPS) >70, could tolerate both the thoracoscopic surgery and pleural biopsy; there were no severe complications. Thoracoscopic findings included pleural hyperaemia, fibrinous adhesion, nodular bulge and fester. The pathological biopsy confirmed diagnoses of malignant tumor (97 cases), tuberculous pleuritis (91 cases), tuberculous empyema (one case), pulmonary schistosomiasis (one case) and unknown etiology (25 cases). The total diagnosis rate was 88.4%. Subcutaneous emphysema occurred in ten cases and fever in six cases, all of which recovered completely with conservative treatment. Conclusions: Flexi-rigid thoracoscopy had a high diagnosis rate, differentiating exudative pleural effusion of unknown etiology with satisfactory effectiveness and safety. There was high degree of relationship between thoracoscopic appearance and primary disease or tumor classification.